1995
DOI: 10.1016/0020-7292(95)02389-t
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocics in developing countries

Abstract: Our results show that an obstetric treatment which is safe when used in certain well-defined indications, may have significant negative effects when used in situations where the same technical quality of care cannot be guaranteed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 11 publications
1
25
1
Order By: Relevance
“…Oxytocin was used routinely to speed up labour, in spite of the risks involved with its use in a situation where labour was not closely monitored. 24 The benefit of accelerating labour is in itself questionable, particularly where the normal duration of labour in a study in another Palestinian hospital was shown to be relatively short. 25 A rising trend in the caesarean section rate (particularly the primary rate) is a real concern for Palestinian women's health, given the tendency to have large families.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin was used routinely to speed up labour, in spite of the risks involved with its use in a situation where labour was not closely monitored. 24 The benefit of accelerating labour is in itself questionable, particularly where the normal duration of labour in a study in another Palestinian hospital was shown to be relatively short. 25 A rising trend in the caesarean section rate (particularly the primary rate) is a real concern for Palestinian women's health, given the tendency to have large families.…”
Section: Discussionmentioning
confidence: 99%
“…8,[24][25][26][27][28] However intramuscular oxytocics administration and the very high episiotomy rates among primiparous women are not in line with international recommendations 29,30 and raise concerns about potential complications.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine rupture is loss of integrity of the myometrium that may result from dehiscence of a prior cesarean delivery scar, dysfunctional or obstructed labor, uterine hyperstimulation with uterotonics, and high parity. When oxytocin or other uterotonic drugs are administered inappropriately to induce or augment labor, particularly by unskilled attendants, there is a risk of uterine hyperstimulation or rupture, increasing the risk of intrapartum hypoxic injury [67,68]. Traditional herbal uterotonics place both the mother and the fetus at risk for hypoxic insult and increase the risk of intra-amniotic infection when inserted directly into the vagina [69][70][71].…”
Section: Uterine Rupturementioning
confidence: 99%